The Effect of Diffusion of Innovation in the Use of Financial Technology (Fintech) in Changes in the Transactions of the Medan City Community - Revika Revika Viola Azzahara; Yohana Ariska Putri Nasution (Penerbit Jurnal Indonesia, 2022)
Along with the times, more and more innovation changes are made by each company in order to get bigger profits and compete to create new things. Therefore, many people are curious and want to try these innovations in order to carry out convenient and easy transaction activities with a more transparent technology system. With Fintech, many people want to know how to use Fintech itself, for the sake of changing activities in people's buying and selling transactions. With the diffusion of this innovation, entrepreneurs/MSMEs provide payments through Fintech because teenagers like modern things. This study aims to find out how big the influence of the diffusion of Fintech innovation on changes in economic activity in transactions in the world of buying and selling, and also the public can feel the benefits of the fintech. Researchers used qualitative methods in conducting this research, and used a descriptive approach, namely the data collection was carried out by documentation, literature study, and interviews with several parties. This study shows the results that many residents, especially the people of Medan City, have implemented fintech in buying and selling transactions.